Intervención del Borde Urbano Barrio Bosque Calderón Tejada mediante la integración del sendero de la quebrada Las Delicias (2022)
The purpose of this degree work is to propose an urban intervention in the delimitation edge of the Bosque Calderón Tejada neighborhood, which will be integrated into the landscape path of the Las Delicias creek, taking into account its physical and social characteristics, such as its functional structure. and services, its ecological and main structure and its socioeconomic structure referring to the social capital of the neighborhood.